The Alzheimer's prevention program : keep your brain healthy for the rest of your life - Small, Gary, 1951- (Workman Publishing, 2012)
"The science-based program, updated with the latest research and discoveries on brain health and lasting memory, is designed to improve mental clarity every day and protect your brain for the rest of your life."--P.[4] of cover.